Management Of Character Education in Madrasah (A Concept and Application) - Mahfudloh, Ririn Inayatul; Mardiyah, Nor; Mulyani, Cici Rumi; Masuwd, Mowafg Abrahem (INJIES: Journal of Islamic Education Studies, 2024)
There is inequality in educational outcomes in terms of graduate behavior such as brawls, corruption, free sex, drugs, theft and other deviant behavior. In fact, several immoral acts were allegedly carried out by the madrasah. Ideally, madrasah students have good behavior because these schools are given more responsibility for educational material than other institutions. Seeing this problem, the government decided that character education should be implemented in schools. This research is feasible for managing character education in madrasas effectively starting from planning, organizing, implementing, monitoring and evaluating. The series of management functions are carried out sequentially with each other, so that the expected character values ​​can be internalized in students' lives with indicators; students know the character, feel the character and are able to do it. Supervision activities focus more on ensuring that activities are carried out in accordance with the plans made at the beginning, while evaluation activities look more at the success of what has been implemented compared to the plans made in advance. Students do not have to be given quantitative grades but what is more important is how far from the integrated values ​​have been internalized in madrasa life